Environmental and Social Impacts of Gajah Mungkur Reservoir Development 1972-1992 - Prasetyo, Muhammad Wahyu; Wasino, Wasino (Universitas Negeri Semarang, 2024)
Reservoirs are artificial containers formed as a result of the construction of dams, with the benefit of storing water on a large scale, and the reservoir water comes from dammed rivers. Many reservoirs are built in Indonesia because the rivers have excess water during the rainy season and have a small water discharge during the dry season. This research discusses the construction of the Gajah Mungkur multipurpose reservoir in Wonogiri, analyzed in terms of impacts and changes that occurred, therefore it was taken that the years 1972-1974 were the years before the construction of the reservoir, then 1974-1981 was the construction period, and to see the changes range from 1981 to 1992. The research method used in this paper is the historical research method. The construction of this multi-purpose reservoir has made the people of Wonogiri feel a change in the environment where previously it was very difficult in the agricultural sector to get fertile land and lots of water. As for the social aspect of society, it certainly brings changes in the population, namely that some residents take part in the village bedhol transmigration to improve their fate.